Characteristics of Islamic religious education assessment instruments - Rini Mulyani; Karimullah; Wahab; Sahrul Sobirin (At Turots: Jurnal Pendidikan Islam, 2024)
Validity, Reliability, Differentiation, Level of difficulty is an important instrument in education so that the data generated can be used properly. Validation is divided into validation of a content, construct. Content validation is an instrument that can be said to be valid if it is in accordance with the curriculum, material and objectives. While construct validity is validity that thinks how the achievement of test items can measure something that will be measured and adjusted to the concepts that have been set. Reliability is determined by the Cronbach's alpha value, if the Cronbach's alpha value of 0.5 can be used for research purposes. Differentiating ability distinguishes the upper and lower groups in the form of questions. The level of difficulty distinguishes questions in terms of difficulty.